ANALISIS PERUBAHAN MAKNA DALAM INTERAKSI DIGITAL PENGGEMAR YOUTUBE SPTRAKORI_OFFICIAL - Meidina Fauziyyah; Tanti Agustiani; Deden Ahmad Supendi (Universitas Batanghari, 2026)
This study investigates semantic shifts in digital communication within a fan community on the YouTube platform. The analysis focuses on language use by korizen in the comment section of the @Sptrakori_Official account. Using Djajasudarma’s (2016) semantic framework, this qualitative study identifies 57 linguistic data. The results indicate that connotative meaning change is the most dominant type (24 data), followed by emotive meaning (15 data), while other types include extended, constructional, idiomatic, lexical, and narrowed meanings. Associative factors are found to be the primary cause of semantic change, occurring in 40 data instances. Notably, no influence of regional languages is identified, indicating that semantic variation in this digital interaction is mainly driven by associative creativity and emotional expression among users.